'Interculturalism as treason': policing, securitization, and neoliberal state formation in Southern Chile. Issue 3 (2nd September 2018) - Risør, Helene; Jacob, Daniela
ABSTRACT: This article offers an ethnographic analysis of Patrullas de Acercamiento a Comunidades Indígenas (Indigenous Community Outreach Patrols, or PACI), a community police initiative of the Chilean police. It situates the program within the broader context of democratization, state-sponsored interculturalism, and neoliberal state formation in contemporary Chile. It shows how the burden of establishing intercultural relations falls upon lower-ranking indigenous officers to argue that in the context of the so-called 'Mapuche conflict' the PACI officials stand out as a potential traitors because they are always at risk of being accused of not being in a 'true' and 'inner' allegiance with either the indigenous communities or the state. Further, we argue that the PACI represents an expansion of the state's presence in the life of the poor indigenous population. This state expansion reinforces contemporary neoliberal policies where focus is on the formation of a state and subjects that comply with the ideals of a free market economy. The analysis of indigeneity in Chile must therefore take seriously this intimate state presence and the consequences it holds for those involved in these processes.